The Relationship Between Electronic Word-of-Mouth and Online Purchase Intention - Ong, Huay Mun; Salim, Siti Aisyah (Research in Management of Technology and Business, 2025)
The Internet and social media platforms have significantly shaped online shopping habits. Electronic word-of-mouth (eWOM), including online ratings and reviews, has become an important aspect of consumer decision-making as it provides easily accessible and versatile information that reduces transaction costs and uncertainty. However, scholars and those working in the sector are still disputing how word-of-mouth affects customers’ likelihood of purchasing online. Even though the use of search engines and online buying has become more common, there is still no consensus about how word-of-mouth (e-WOM) affects purchases. Hence, this research aims to identify the dimensions of electronic word-of-mouth that are rated highly by online consumers in Malaysia, the level of online purchase intention, and the relationship between electronic word-of-mouth and online purchase intention among online consumers in Malaysia. The Information Adoption Model (IAM) has been selected as the theoretical framework for this study. The population of this study consisted of 5.97 million individuals between the ages of 25 and 34 using online shopping platforms such as Shopee, Lazada, and TikTok. This study uses a quantitative method, a questionnaire distributed by Google Forms to collect data. This study has collected data from 333 respondents among online consumers in Malaysia with a response rate of 87%. All the collected data were analysed using the Statistical Package for Social Science (SPSS) and presented in frequency, mean, and standard deviation. Besides, the hypotheses were tested using Spearman’s Correlation Coefficient with the help of the Statistical Tool for Social Science (SPSS). As a result, all variables had a positive and significant relationship with online purchase intention and all hypotheses were accepted. The highest correlation coefficient is 0.982, indicating that brand image has a strong and significant relationship with online purchase intention. The results emphasise the importance of eWOM in shaping online purchase intentions and provide marketers and companies valuable information to improve their strategies for influencing customer behaviour.